(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2025)
Scientific knowledge has developed not in a straight, cumulative line but through radical transformations called scientific revolutions. Thomas S. Kuhn, in The Structure of Scientific Revolutions, describes a paradigm as the guiding framework of scientific inquiry. A paradigm shift occurs when existing theories fail to address emerging anomalies, creating a crisis that gives rise to a new conceptual order. This study explores the relevance of Kuhn’s paradigm theory to Islamic epistemology in addressing modern intellectual challenges. Using qualitative library research and descriptive-deductive analysis, it draws primarily on Kuhn’s work, alongside literature in the philosophy of science and contemporary Islamic thought. The findings reveal that Kuhn’s framework offers an adaptable lens for interpreting the evolution of Islamic scholarship without neglecting the normative authority of the Qur’an and Hadith. Hence, his ideas can inform strategies for renewing Islamic thought to be more contextual, critical, and responsive to present realities.